Functional interactions between management of arable field margins and soil mesofauna - Carlesso, Lea (2019)
The damage to soils caused by agricultural intensification greatly affects belowground faunal communities, typically via a reduction in population size and diversity in comparison with those in semi-natural habitats. This can cause an imbalance in associated soil functions. The soil mesofauna, including Acari (mites) and Collembola (springtails), fulfil a wide range of these functions and our understanding of soil processes is closely linked to our knowledge of the dynamics of invertebrate communities. In the context of current global change, sustainable food production is a significant challenge that can potentially be better met by improved understanding of the abundance and composition of the soil mesofaunal populations, in order to optimize ecosystem services delivered by agricultural soils.